Peru. 1956. Unnamed Summit Approx. 18,000 ft. - Kodak Limited (1957)
Person standing, with climbing rope and ice axe, and snow-covered summit in background.
Photograph taken by unidentified person in Peru in 1956 and developed by Kodak London in 1957. Item came in protective white paper sleeve.
Keywords: Mountaineering; Peru; Photographic prints -- Irish -- 20th century